A study on the higher moments of a biased estimator / Ng Set Foong, Low Heng Chin and Quah Soon Hoe - Ng, Set Foong; Low, Heng Chin; Quah, Soon Hoe (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2008)
In this paper, the biased estimator that is derived in Ng, Low, and Quah (2007) is further studied. The expression for the higher moments of the estimator is important if we want to know the whole sampling properties of the estimator. Hence, a general expressionfor the higher moments of the estimator is derived in this paper. Furthermore, the bias, variance, mean squared error, skewness and kurtosis of the estimator are derived from the higher moments of the estimator.